Analytic method for evaluating players` decisions in team sports: Applications to the soccer goalkeeper - Lamas, L.; Drezner, R.; Otranto, G.; Barrera, J. (PLOS ONE, 2018)
The aim of this study was to define a method for evaluating a player`s decisions during a game based on the success probability of his actions and for analyzing the player strategy inferred from game actions. There were developed formal definitions of i) the stochastic process of player decisions in game situations and ii) the inference process of player strategy based on his game decisions. The method was applied to the context of soccer goalkeepers. A model of goalkeeper positioning, with geometric parameters and solutions to optimize his position based on the ball position and trajectory, was developed. The model was tested with a sample of 65 professional goalkeepers (28.8 ± 4.1 years old) playing for their national teams in 2010 and 2014 World Cups. The goalkeeper`s decisions were compared to decisions from a large dataset of other goalkeepers, defining the probability of success in each game circumstance. There were assessed i) performance in a defined set of classes of game plays; ii) entropy of goalkeepers` decisions; and iii) the effect of goalkeepers` positioning updates on the outcome (save or goal). Goalkeepers` decisions were similar to the ones with the lowest probability of goal on the dataset. Goalkeepers` entropy varied between 24% and 71% of the maximum possible entropy. Positioning dynamics in the instants that preceded the shot indicated that, in goals and saves, goalkeepers optimized their position before the shot in 21.87% and 83.33% of the situations, respectively. These results validate a method to discriminate successful performance. In conclusion, this method enables a more precise assessment of a player`s decision-making ability by consulting a representative dataset of equivalent actions to define the probability of his success. Therefore, it supports the evaluation of the player`s decision separately from his technical skill execution, which overcomes the scientific challenge of discriminating the evaluation of a player`s decision performance from the action result.